Baja autoestima en la infancia y la influencia del síndrome del impostor de una persona de la Ciudadela Primero de Diciembre de Babahoyo - Zambrano Fuentes, Lenin Jose (2020)
When we speak of low self-esteem or lack of self-esteem, we refer to a perception of ourselves that prevents us from perceiving ourselves as valuable, talented people or simply having an objective judgment about who we are. This means that as we grow older and if we do not take the necessary precautions, we can become severe with ourselves. Having low self-esteem does not mean, however, that the person constantly acts according to that criterion: people are complex, we have multiple faces and it is not always easy to determine the elements that make up our personality. Nor should low self-esteem be confused with mental illnesses or more complicated mood ailments, such as depression, etc. Consequently, children who have presented low self-esteem are more likely to suffer from imposter syndrome years later, triggering a number of fears, complexes and negative ideas towards themselves, they live in fear that one day someone will discover that they are not They are as "good" as they think, since they assimilate success or positive performance as something they have achieved by chance or luck and not on their own merits.